KELAYAKAN FLIPCHART PADA BUAH ANGKAM, PEH NGAN, DAN TAPA’ KERA MATERI BERBAGAI TINGKAT KEANEKARAGAMAN HAYATI - Jemmi Jemmi; Entin Daningsih; Titin Titin (Universitas Tanjungpura, 2018)
AbstractLearning media was a tool that can be used in the delivery of learning material, making it easier for students to understand the learning material. This study aimed to determine the feasibility media flipchart of morphology and nutritional value of angkam, peh ngan, and tapa’ kera fruits on materials of various levels of biodiversity of Indonesia class X SMA with three sub material that consists of the concept of biodiversity Indonesia, classification of living things, the effort of conservation and utilization of biodiversity. This research was a descriptive research. Validator selection in this research was done by using purposive sampling and data collection was done using an instrument validation. Validation was done by five validators, two validators was lecturers of biology education, while three other validators an X-class high school biology teacher who uses the curriculum in 2013 in the city of Pontianak. The results of the flipchart validation with 9 criteria obtained the value of the CVR and CVI of 0.99 corresponds to the value of the CVR minimum Lawshe to five validator that was 0.99, so the flipchart media considered valid and declared eligible as a medium of learning in matter of various levels of biodiversity of Indonesia X-class high school with three sub material consisting of the concept of biodiversity Indonesia, classification of living things, the conservation and utilization of biodiversity.Keywords: Flipchart, Nutritional content, Morphology, Biodiversity